2017
DOI: 10.3389/fpsyg.2017.00766
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State fMRI Associated with Stop-Signal Task Performance in Healthy Middle-Aged and Elderly People

Abstract: Several brain regions and connectivity networks may be altered as aging occurs. We are interested in investigating if resting-state functional magnetic resonance imaging (RS-fMRI) can also be valid as an indicator of individual differences in association with inhibition performance among aged (including middle-aged) people. Seventy-two healthy adults (40–77 years of age) were recruited. Their RS-fMRI images were acquired and analyzed via two cluster-analysis methods: local synchronization of spontaneous brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
0
16
1
Order By: Relevance
“…During the go/no-go task, abnormal activation in the left IFG was also found in smokers and healthy subjects, while patients with a left IFG lesion showed impaired control performance (Fassbender et al, 2004 ; Swick et al, 2008 ; Luijten et al, 2013 ). Even in resting-state, spontaneous activity in the left IFG was significantly correlated with SSRT (Tian et al, 2012 ; Lee and Hsieh, 2017 ). The bilateral IFG activation in response to inhibition process in both control and LPE groups also provides support that the process of control response may require the involvement of the left and right IFG together.…”
Section: Discussionmentioning
confidence: 99%
“…During the go/no-go task, abnormal activation in the left IFG was also found in smokers and healthy subjects, while patients with a left IFG lesion showed impaired control performance (Fassbender et al, 2004 ; Swick et al, 2008 ; Luijten et al, 2013 ). Even in resting-state, spontaneous activity in the left IFG was significantly correlated with SSRT (Tian et al, 2012 ; Lee and Hsieh, 2017 ). The bilateral IFG activation in response to inhibition process in both control and LPE groups also provides support that the process of control response may require the involvement of the left and right IFG together.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing this paradigm, researchers have observed decreased motor inhibition in various clinical disorders, such as attention deficit hyperactivity disorder [5] and substance use disorders [6,7]. The deficiency in motor inhibition can also be found in normal aging [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the right-hemisphere dominance in activation is well-known, some studies have also reported bilateral activation in IFG, MFG, SMA and MTG (Li et al, 2006 ; Cohen et al, 2010 ; Congdon et al, 2014 ). Furthermore, Lee and Hsieh ( 2017 ) have found that the regional homogeneity/fractional amplitude of low-frequency fluctuation and SSRT were significantly negative correlated in the left IFG. The L_MFG and L_IFG_tri contributed the most to the coefficient of determination of the linear regression model in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Poor response inhibition may profoundly interfere with the requirements of everyday life. Inhibitory control is also an important function in individual daily activities, such as being able to stop driving upon seeing a pedestrian unexpectedly cross the road (Lee and Hsieh, 2017 ). However, sleep deprivation (SD) for one night can impair the performance of inhibitory control (Chuah et al, 2006 ; Zhao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%